Pengembangan Media Fruits Vocabulari Berbasis Mobile App Untuk Meningkatkan Keterampilan Membaca Kosa Kata Bahasa Inggris Kelas III Sd - Adinda Puspitasari; Ulhaq Zuhdi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The low interest in learning and achievement of basic English competencies in third grade elementary school students is often triggered by the use of monotonous conventional teaching methods. As a solution, this study aims to develop interactive learning media based on mobile apps on fruits vocabulary material, while testing the level of validity, practicality, and effectiveness in improving students' vocabulary reading skills. This study applies the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. A total of 14 third grade students of SDN Tlogorejo Kepohbaru were involved as trial subjects. Data were collected through expert validation sheet instruments (material and media), student response questionnaires, and learning outcome tests (pretest and posttest). The research findings confirm that: (1) The learning media for fruits vocabulary material is categorized as Very Valid, with a feasibility percentage of 89.23% from material experts and 87.14% from media experts; (2) The media is considered Very Practical based on the average score of the student response questionnaire of 91.63%; (3) The media has been proven to be effective in significantly improving learning outcomes based on a paired t-test, where the average value jumped from 49.41 (pretest) to 83.85 (posttest) with a significance level of 0.000 ($Sig. < 0.05$). Thus, this mobile-based learning application is feasible and effective for optimizing elementary school students' English vocabulary reading skills.